Cyprus : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1995)
This paper reviews economic developments in Cyprus during 1990-95. Economic growth slowed down and became more volatile in the early 1990s compared with the 1980s. External shocks, compounded by unfavorable domestic developments, kept GDP growth at unusually low levels in 1991 and 1993. Inflation, which had remained below the European Union (EU) average throughout the 1980s, edged over it since 1991. The price deceleration in 1993 and 1994 was insufficient to bring Cypriot inflation in line with falling inflation in the EU, mostly on account of the introduction of value-added tax in 1992.